(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
As an obligation to protect the children, both physically and mentally, every child must be provided inaccordance with their welfare by providing guarantees for the fulfillment of children’s rights. The Indonesiangovernment’s concern for the protection and fulfillment of children’s rights has actually existed since theenactment of Law Number 4 of 1979 concerning Child Welfare. However, until the promulgation of theChild Protection Act to date, welfare and fulfillment of children’s rights are still far from what they shouldbe, mostly for street children and neglected children. The purpose of this research is to study how the effortsto fulfill children’s rights through the program specifically for street children and neglected children. Themethod used in this research is normative juridical. Based on the results of the study, that the KampungAnak Negeri Program in Surabaya was made as a social service for the fulfillment of children’s rights in theorphanage system, including meeting the needs of food, clothing, and shelter, as well as mental and spiritualguidance, behavior, children’s talents, and business skills that can improve child welfare after leaving later.